Risk of al-Bai’ on Clove Seeds in Mappalla System Islamic Law Perspectives - Anita, Anita; Fikri, Fikri; Sunuwati, Sunuwati (IAIN Parepare, 2020)
This study focuses on al-bai’ on clove seeds in the system mappalla perspective of Islamic law. This type of research is qualitative. The research was conducted descriptively-qualitatively. The research location was conducted in Bukkere, Sidrap Regency. The results show that al-bai’ on clove seeds in the system m appalla performed by the people of Bukkere is a hereditary tradition that has become al-urf ; al-bai’ on clove seeds in the mappalla system found there is an element of gharar in Islamic law; al-bai’ on clove seeds in the system mappalla, can not guarantee a good growth that can harm one party.